Performance Photo SDhoot (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
Information about the theatrical production staged in 2025 by students from the Center for the arts at the State University of SC (UDESC). Directed by Tefa Polidoro and  Elaine Nascimento.
Keywords: theatrical production; scenic creation